The use of low intensity pulsed ultrasound in the foot and ankle. Issue 4 (April 2021) - Rashid, Mustafa S.; Tourné, Yves; Teoh, Kar H.
Abstract : Low intensity pulsed ultrasound (LIPUS) therapy has demonstrated clinical effectiveness in achieving union in a variety of fracture situations. Few studies have investigated the effectiveness of LIPUS therapy in foot and ankle surgery. The overall rate of union in all published studies relating to the use of LIPUS in a variety of foot and ankle fracture and fusion situations is 95%. Some studies suggest lower healing rates ( 67%) when LIPUS therapy is used to treat hindfoot fusion nonunion. A well-powered, high-quality, randomized controlled trial is needed to demonstrate the clinical and cost effectiveness of LIPUS therapy in foot and ankle surgery. Cite this article: EFORT Open Rev 2021;6:217-224. DOI: 10.1302/2058-5241.6.200045